Critical Appraisal of Clinical Practice Guidelines for Age-Related Macular Degeneration - Annie M. Wu; Connie M. Wu; Benjamin K. Young; Dominic J. Wu; Curtis E. Margo; Paul B. Greenberg (Journal of Ophthalmology)
Purpose. To evaluate the methodological quality of age-related macular degeneration (AMD) clinical practice guidelines (CPGs). Methods. AMD CPGs published by the American Academy of Ophthalmology (AAO) and Royal College of Ophthalmologists (RCO) were appraised by independent reviewers using the Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument, which comprises six domains (Scope and Purpose, Stakeholder Involvement, Rigor of Development, Clarity of Presentation, Applicability, and Editorial Independence), and an Overall Assessment score summarizing methodological quality across all domains. Results. Average domain scores ranged from 35% to 83% for the AAO CPG and from 17% to 83% for the RCO CPG. Intraclass correlation coefficients for the reliability of mean scores for the AAO and RCO CPGs were 0.74 and 0.88, respectively. The strongest domains were Scope and Purpose and Clarity of Presentation. The weakest were Stakeholder Involvement (AAO) and Editorial Independence (RCO). Conclusions. Future AMD CPGs can be improved by involving all relevant stakeholders in guideline development, ensuring transparency of guideline development and review methodology, improving guideline applicability with respect to economic considerations, and addressing potential conflict of interests within the development group.